2022
DOI: 10.3390/app12073290
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Extract Affecting the Transformation of Biogenic Tooeleite and Its Stability

Abstract: Highly toxic As(III) is the main form of As in wastewater. The retention of As by tooeleite has gradually attracted attention in recent years due to its great potential for the direct removal of As(III). The existence of natural As-bearing minerals is closely related to microorganisms and organic matters. In this study, yeast extract was found to enhance the stability of biogenic tooeleite by Acidithiobacillus ferrooxidans (A. ferrooxidans). The effects of pH, Fe/As and yeast extract concentration were systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…A study conducted by Hakobyan et al (2012) proved that the addition of this ingredient to the Rhodobacter sphaeroides medium could increase cell growth and photoproduction of hydrogen by the bacterium strain isolated from mineral springs. In addition, another report also stated that yeast extract can increase the stability of biogenic tooeleite by the bacterium Acidithiobacillus ferrooxidans, thereby reducing highly toxic soluble arsenite (III) (Li et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Hakobyan et al (2012) proved that the addition of this ingredient to the Rhodobacter sphaeroides medium could increase cell growth and photoproduction of hydrogen by the bacterium strain isolated from mineral springs. In addition, another report also stated that yeast extract can increase the stability of biogenic tooeleite by the bacterium Acidithiobacillus ferrooxidans, thereby reducing highly toxic soluble arsenite (III) (Li et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The peak at 815.14 eV was corresponded to the Fe-O-As vibrational peak, indicating that As(III) removal process occurred through surface complexation, as well as solid-phase precipitation by bonding As(III) to Fe [62]. The results suggested that the nZVI/MXene@CNTs retained a good magnetic characteristic, making it suitable for recycling [63,64]. In order to further investigate the adsorption mechanism of nZVI/MXene@CNTs, the XPS analysis was performed before and after the adsorption of As(III).…”
Section: Mechanism Analysismentioning
confidence: 94%
“…A recent report stated that the stability of Acidithiobacillus ferrooxidans to the biological source of oil was significantly improved under the action of yeast extract as a culture additive. It reduces the leaching concentration of arsenic (As), a highly toxic waste in acid water, from 13.78 mg/l to 7.23 mg/l, and improves the stability by 40%, which is of great significance to the control of arsenic content [98].…”
Section: Applications In Biotechnologymentioning
confidence: 99%